The role of Post-New Public Management in shaping innovation: the case of a public hospital. (December 2022) - Melo, Sara; De Waele, Lode; Polzer, Tobias
This article examines how the Post-New Public Management administrative model adopted by a teaching hospital in Portugal shapes innovation processes. We find that innovation is a multi-level organizational phenomenon that relies substantially on the interplay of three factors: (1) trust-based professional autonomy at the individual level; (2) an intra-organizational collaborative approach in innovation (re)design at the team level; and (3) staff involvement/commitment towards the hospital's strategy in the implementation of innovations at the organizational level. Additionally, innovation is facilitated by interconnected formal and informal processes that mutually reinforce each other. The study contributes to the literature on innovation and administrative models by providing a nuanced understanding of how intra-organizational innovation processes take place within a Post-New Public Management model. As such, it is one of the first attempts to empirically analyse and link the administrative model of Post-New Public Management with innovation. Points for practitioners: This research provides an account of how a Post-New Public Management administrative model can foster intra-organizational innovation through collaboration across different hierarchies and professions. The article also helps to better understand the role of organizational dynamics at individual, team and organizational levels on innovation, as well as how these can shape and be shaped by formal and informal processes.